Effect of Personality Traits and Social Value Orientation on The Tendency to Dishonesty”: An Empirical Study - David MARTINCIK; Olga MARTINCIKOVA SOJKOVA (Communications of International Proceedings, 2023)
The tendency for dishonesty and cheating engenders efficiency losses, manifesting in various forms, such as non-compliance with established production protocols or instances of tax evasion. Cumulatively, the compounding effect of numerous small acts of dishonesty culminates in substantial damage. The behavioral economics literature documents that people tend to commit small frauds but rarely resort to large frauds. We conducted a series of well-known experiments and quasi-experiments measuring propensity to cheat, social orientation, and personality traits. To measure the tendency toward dishonesty, we conducted a coin-flip experiment. Additionally, we utilized quasi-experimental methods to calculate social orientation through a brief six-question version of the Social Value Orientation Measurement and a short ten-question version of the Big Five personality traits. Trust in others was included as an explanatory variable derived from a sender-receiver experiment. Employing Poisson regression analysis, we discern the dependence of the tendency for dishonesty on social orientation. Our findings reveal a correlation between social orientation and the propensity for dishonesty. Specifically, individuals with a more competitive disposition exhibit a heightened inclination to engage in dishonest behaviors compared to their prosocial counterparts. However, our analysis did not detect any dependence on trustworthiness or personality traits to the tendency for dishonesty.
Keywords: Experimental economics; dishonesty; personality traits; social value orientation; trust in others